1996
DOI: 10.1152/ajpgi.1996.271.4.g640
|View full text |Cite
|
Sign up to set email alerts
|

Parietal cell MAP kinases: multiple activation pathways

Abstract: Epidermal growth factor (EGF) is a potent mitogen for many cell types; however, the best known effect of EGF on gastric parietal cell HCl secretion is inhibition of this response. Using rabbit parietal cells in primary culture, we recently showed that the effect of EGF is biphasic with acute inhibition followed by sustained enhancement of acid secretory-related responses. We hypothesized that EGF might activate a mitogen-activated protein (MAP) kinase signaling pathway in parietal cells, and this pathway might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
4
19
0
1
Order By: Relevance
“…While several studies have found that wortmannin (10 -15) or dominantnegative PI 3-kinase (9) effectively inhibits activation of the MAP kinase cascade, many other studies have found that inhibition of PI 3-kinase has no effect on the activation of Erk proteins (17)(18)(19). The results in Fig.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…While several studies have found that wortmannin (10 -15) or dominantnegative PI 3-kinase (9) effectively inhibits activation of the MAP kinase cascade, many other studies have found that inhibition of PI 3-kinase has no effect on the activation of Erk proteins (17)(18)(19). The results in Fig.…”
Section: Discussionmentioning
confidence: 84%
“…A recent study found that overexpression of the p110␥ type of PI 3-kinase resulted in the activation of Erk, but that p110␣ did not (9). Inhibition of PI 3-kinase with wortmannin (10 -16) or dominant-negative PI 3-kinase (9) has been shown to block activation of MAP kinase in some but not all cells (17)(18)(19).…”
Section: Pimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, overexpression of a constitutively active p110-␣, a PI3-K isoform, has been shown to activate the Ras-ERK pathway in at least one system (31), but not in others (22,37,42,47). In addition, many studies have demonstrated a requirement of PI3-K activity for ERK activation by multiple diverse stimuli (13,16,17,25,40,47,76,86,89,91), while other reports failed to show a sensitivity of some of these same stimuli to PI3-K inhibitors (59,78,85,92). One explanation for these apparent discrepancies may be that the ability of PI3-K inhibitors to block ERK activation is dependent on the cell type, type of stimuli, and strength of the signal (17,100).…”
mentioning
confidence: 99%
“…In particular, we and others have shown that carbachol induces the ERKs (36,47,48), the c-Jun NH 2 -terminal kinases (JNKs) (35), and p38 kinase (37), molecules known to regulate multiple important physiological functions in the parietal cells. Whereas the ERKs and p38 kinase appear to be involved in the process of gastric acid production (37,48), activation of the JNKs seems to be an important step in the response of the parietal cells to stress and inflammation (35).…”
Section: Discussionmentioning
confidence: 99%